Estimation of dementia prevalence at the local level in the United States - Erin E. Bennett; Abraham Kwan; Kan Z. Gianattasio; Brittany Engelman; N. Maritza Dowling; Melinda C. Power (Alzheimer’s & Dementia: Translational Research & Clinical Interventions, 2021)
Abstract Introduction Ensuring adequate and equitable distribution of resources to support persons living with dementia relies on understanding the burden and distribution of dementia in a population. Our goal was to develop an approach to estimate dementia prevalence at the local level in the United States using publicly available data. Methods Our approach combines publicly available data on dementia prevalence and demographic data from the US Census to estimate dementia prevalence. We illustrate this approach by estimating dementia prevalence in persons aged 65 and older in Philadelphia, PA; Chicago, IL; and Atlanta, GA. Results Overall, we estimate the prevalence of dementia among those 65 and older to be 11.9% in Philadelphia, 11.8% Chicago, and 12.3% in Atlanta. Estimates across Philadelphia localities vary from 9.3% to 15.9%. Discussion Our approach provides a cost‐effective method to generate estimates of dementia prevalence at the local level. HIGHLIGHTS Brain health needs assessments require understanding of local dementia prevalence. Our approach can be used to estimate dementia prevalence in individual communities. This information can inform decisions about distribution of resources.